Optimization Analysis of Structure Parameter of Angular- contact Ball Bearings based on Fatigue Life - Ye Zhenhuan; Liu Zhansheng; Wang Liqin (Jixie chuandong)
According to calculated method of bearing fatigue life based on micro- area contact,a optimization model of structure parameters of angular- contact ball bearings is established. Taking an angular- contact ball bearing used in certain gas- turbine engine as the example,the influence rule of structure parameter on maximum contact stress,fatigue life and cage sliding ratio is analyzed. And the optimization scheme is further proposed based on the purpose of lifetime extension of bearings. The analysis results could provide reference for structure design of angular- contact ball bearing.